2021
DOI: 10.3389/fpsyt.2021.665507
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Post-traumatic Stress Symptoms and Its Associations With Quality of Life, Demographic and Clinical Characteristics in COVID-19 Survivors During the Post-COVID-19 Era

Abstract: Background: The prevalence of post-traumatic stress symptoms (PTSS) in COVID-19 survivors is unclear. This study examined the prevalence of PTSS and its association with quality of life (QOL) among COVID-19 survivors during the post-COVID-19 era in China.Methods: This was a comparative, cross-sectional study. PTSS, depressive symptoms, and QOL were assessed with standardized instruments.Results: A total of 134 COVID-19 survivors and 214 non-infected controls (healthy controls hereafter) were recruited. Among C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“… 7 A previous study found that 18.66% (95% CI 11.98 to 25.34) of COVID-19 survivors displayed symptoms of PTSD. 8 Highly similar prevalences of PTSD among COVID-19 patients, healthcare workers and the general population were also reported in other systematic reviews. 9 , 10 Besides the high rate of PTSD, COVID-19 patients presented a considerable proportion of depression, anxiety, distress and sleep disturbances.…”
Section: Introductionsupporting
confidence: 72%
“… 7 A previous study found that 18.66% (95% CI 11.98 to 25.34) of COVID-19 survivors displayed symptoms of PTSD. 8 Highly similar prevalences of PTSD among COVID-19 patients, healthcare workers and the general population were also reported in other systematic reviews. 9 , 10 Besides the high rate of PTSD, COVID-19 patients presented a considerable proportion of depression, anxiety, distress and sleep disturbances.…”
Section: Introductionsupporting
confidence: 72%
“…While most studies reported more severe mental health disorders in infected compared to non-infected individuals, some studies did not reveal this pattern. Some representative findings from the majority of studies are as follows: (1) Prevalence of post-traumatic stress symptoms was more severe in COVID-19 survivors compared to healthy controls[ 91 ]; (2) Anxiety and depression were more prevalent in infected compared to non-infected people in a large Chinese sample[ 92 ]; (3) “Prevalence of stress, anxiety, depression, intrusion, hypervigilance, and avoidance among infected health care workers (HCWs) were significantly higher in comparison to non-infected HCWs”[ 93 ]; and (4) Suicidal ideation was more prevalent in infected vs non-infected individuals, in the United States[ 27 ]. Even months after recovery from the infection, depression, anxiety, and PTSD were prevalent[ 94 ].…”
Section: Comparisons Of Mental Health Symptomatology Between Infected...mentioning
confidence: 99%
“…The COVID-19 pandemic is a global traumatic events (1), which has caused more than 248 million cases, and resulted in more than 5 million deaths worldwide. Nevertheless, the COVID-19 pandemic has also led to a "mental health tsunami", including depression (2)(3)(4)(5), anxiety (6)(7)(8)(9)(10)(11)(12), PTSS (13)(14)(15)(16)(17), and poor sleep quality (18)(19)(20)(21)(22)(23). PTSD (or PTSS) is one of the most common mental distress among this tsunami.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is a common but easily overlooked comorbidity among MDD patients in the face of global traumatic events of COVID-19. Many recent studies have focused on PTSS or PTSD during COVID-19, but these previous studies have mainly focused on COVID-19 survivors (9)(10)(11), hospital staff (3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), teachers (28), and the general population (29)(30)(31)(32)(33). However, few researchers have focused on PTSS co-morbidity in MDD patients during the COVID-19 pandemic (34).…”
Section: Introductionmentioning
confidence: 99%